2018
DOI: 10.3390/nu10101335
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a Healthy Diet in Young Adults: The Role of Nutrition Labelling

Abstract: The use of the nutrition facts label has been associated with healthy eating behaviors for adults. However, the relationship between nutrition facts label use and overall diet quality is not well known in young adults, a vulnerable group that acquire lifelong eating behaviors during this period of life. This study aimed to assess if the use of information on the nutrition facts label is associated with a higher diet quality in young adults. In this cross-sectional study, 958 university students aged 18–34 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 46 publications
(60 reference statements)
5
29
0
3
Order By: Relevance
“…Evidence supports that interventions during this stage of life are pivotal for later health, reducing the risk of chronic diseases [ 12 ]. Young adults have often been reported to have unhealthy dietary habits including higher consumption of fast food, sugar-sweetened beverages, and alcohol [ 13 , 14 , 15 ]. They have also been shown to be the age groups most associated with a deteriorated MedDiet profile [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supports that interventions during this stage of life are pivotal for later health, reducing the risk of chronic diseases [ 12 ]. Young adults have often been reported to have unhealthy dietary habits including higher consumption of fast food, sugar-sweetened beverages, and alcohol [ 13 , 14 , 15 ]. They have also been shown to be the age groups most associated with a deteriorated MedDiet profile [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating habits are essential to achieve physical and intellectual development, as well as to prevent cardiovascular health problems resulting from the impoverishment of the diet [25]. In fact, Cervera, Serrano, Vico, Milla, and García (2013) [26] highlight that the diet followed by the university population is based on malnutrition, suppression of essential foods, and the intake of refined sugars and foods high in fat [27]. It is at this point that adherence to the Mediterranean Diet (MD) comes into play, as multiple studies show that MD is related to health benefits, such as increased life expectancy, adherence to physical activity, and decreased cardiovascular and psychological diseases [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aerobic exercise can be used to medicate of primary dysmenorrhea. 11 It is different from the research conducted by Moradpour that found that there was no significant examined change of the 8-week aerobic exercise on dysmenorrhea. 12 The Covid-19 pandemic has not only changed physical activity but also changed people's dietary habits.…”
Section: Introductionmentioning
confidence: 70%